Progress of research on Traditional Chinese Medicine characteristic nursing of patients with cognitive impairment after stroke (脑卒中后认知障碍的中医特色护理研究进展) - LI Wenya (李文雅); XIAO Chun (肖纯); HUANG Lu (黄璐); PENG Xiaoling (彭晓玲) (中西医结合护理)
This paper expounds the concepts of Traditional Chinese Medicine (TCM) characteristic nursing and post-stroke cognitive impairment, analyzes the etiology and pathogenesis of post-stroke cognitive impairment, reviews the application status of TCM characteristic nursing in the care of patients with post-stroke cognitive impairment, studies its application, looks forward to its development trend, and provides a broader perspective for the clinical care of PSCI patients. (本文阐述中医特色护理及脑卒中后认知障碍相关概念, 分析脑卒中后认知障碍病因病机, 综述中医特色护理在脑卒中后认知障碍患者护理中的应用现状, 展望其发展趋势, 旨在为PSCI患者的临床护理提供参考。)